The Impact of FFC-AL-EIT-D in Assisted Living during the COVID-19 Pandemic. Issue 4 (2nd October 2022) - Resnick, Barbara; Galik, Elizabeth; McPherson, Rachel; Vigne, Erin; Holmes, Sarah
ABSTRACT: The purpose of this study was to test the preliminary effectiveness and feasibility of implementation of Function Focused Care for Assisted Living Using the Evidence Integration Triangle in Assisted Living Communities with Residents with Dementia (FFC-AL-EIT-D) during the pandemic. This was a single group pre-post study design including 51 communities in a single state. The communities ranged in size from 8 to 50 residents with a mean of 13 (SD = 7). The majority (99%) were for profit. Following implementation of FFC-AL-EIT-D there was significant improvement in environments and policies supporting physical activity and some evidence suggesting they used new supplies to engage residents in physical activity. There was no change in falls, emergency room, hospital, or nursing home transfers.